2021
DOI: 10.3389/fimmu.2021.738788
|View full text |Cite
|
Sign up to set email alerts
|

Rituximab Immunomonitoring Predicts Remission in Membranous Nephropathy

Abstract: Primary membranous nephropathy (pMN) is an autoimmune kidney disease and a common cause of nephrotic syndrome in adults. Rituximab is becoming a first line therapy for patients with persistent nephrotic syndrome with proven safety and efficacy, achieving remission in 60%–80% of cases. For the remaining 20%–40% of patients there is an urgent need to identify early biomarkers of resistance to rituximab to adapt therapeutic management. In nephrotic patients, rituximab is found in the blood more transiently than i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
18
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 18 publications
(21 citation statements)
references
References 37 publications
2
18
1
Order By: Relevance
“…Rituximab underdosing is not uncommon in pMN ( 63 , 64 ). Indeed, rituximab bioavailability is significantly decreased in pMN compared to other non-nephrotic autoimmune diseases due to the binding of rituximab to albumin and its wasting in the urine ( 63 , 65 , 66 ).…”
Section: Rituximab-refractory Membranous Nephropathymentioning
confidence: 99%
See 3 more Smart Citations
“…Rituximab underdosing is not uncommon in pMN ( 63 , 64 ). Indeed, rituximab bioavailability is significantly decreased in pMN compared to other non-nephrotic autoimmune diseases due to the binding of rituximab to albumin and its wasting in the urine ( 63 , 65 , 66 ).…”
Section: Rituximab-refractory Membranous Nephropathymentioning
confidence: 99%
“…Indeed, rituximab bioavailability is significantly decreased in pMN compared to other non-nephrotic autoimmune diseases due to the binding of rituximab to albumin and its wasting in the urine ( 63 , 65 , 66 ). We have shown that rituximab was undetectable three months (month-3) after rituximab infusion (two 1 g infusions two weeks apart) in 56% of nephrotic pMN, these patients were less likely to achieve clinical and immunological remission ( 64 ). Patients with the most severe nephrotic syndrome – with a baseline albumin level of less than 22.5 g/L – were more likely to have an undetectable serum rituximab level at month-3 ( 64 ).…”
Section: Rituximab-refractory Membranous Nephropathymentioning
confidence: 99%
See 2 more Smart Citations
“…It is also unclear what the optimal dosing strategy of rituximab is. Importantly, patients with higher proteinuria and lower serum albumin at time of rituximab infusion show lower residual serum rituximab levels at month-3 ( 102 ), and this was associated with subsequent lower response rates ( 103 ). These findings support the idea that rituximab dose can affect the response, especially in patients with higher proteinuria.…”
Section: How To Treat Patients With Pmn?mentioning
confidence: 99%